The Analysis of the Learning Efficiency of Bidikmisi Students - Kuswanto Kuswanto (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2019)
This study aims to determine the factors that influence student learning outcomes and the level of efficiency of the use of these inputs. Respondents in this study were the recipients of the 2015 - 2017 Bidikmisi class at the PIPS Department of the University of Jambi FKIP, namely 53 people. This study uses quantitative methods. Data were analyzed using the Stochastic frontier production function approach. The results showed that, first the use of books / modules had a positive and significant effect on the learning output of bidikmisi recipient students. Second the use of material photocopy material has a positive and significant effect on learning output. And, third, the use of pulses for internet access has a positive and significant effect. The level of student learning efficiency in using learning inputs averaged 94 percent. Student learning inefficiency is influenced by organizational activities and interaction with Bidikmisi managers, significant at Î± = 5 percent.